BOUNDARY LAYER CLIMATES - Oke, T. R., author 247485 (New York : Methuen & Co., 1987)
This modern climatology textbook explains the climates formed near the ground in terms of the cycling of energy and mass through systems. It begins with a discussion of atmospheric processes, and how they interact with the physical properties of surfaces to produce distinctive climates. This provides the conceptual framework for the subsequent analysis of the climates of a wide range of natural and man-modified environments, extending from the micro-scale of insects and leaves up to the local scale of cities and regional air pollution. In this second, expanded edition, Professor Oke provides a fuller description of atmospheric layers, and gives more emphasis to the whole planetary boundary layer. There are nearly 50 new figures and new material on radiation geometry, thermals, convective cloud, leaf-air exchange, evapotranspiration from crops and forests< effects of topography on airflow, and the energy balance of cities.